2017
DOI: 10.1155/2017/3726595
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation as a Noninvasive Epigenetic Biomarker for the Detection of Cancer

Abstract: In light of the high incidence and mortality rates of cancer, early and accurate diagnosis is an important priority for assigning optimal treatment for each individual with suspected illness. Biomarkers are crucial in the screening of patients with a high risk of developing cancer, diagnosing patients with suspicious tumours at the earliest possible stage, establishing an accurate prognosis, and predicting and monitoring the response to specific therapies. Epigenetic alterations are innovative biomarkers for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 82 publications
0
74
0
3
Order By: Relevance
“…Because the sample size of type 2 PRCC from TCGA-KIRP is small, we have not divided samples into training and validation sets, thus the differentially methylated sites we identified require validation as part of future studies. In addition, while the DNA methylation markers in our present study were identified from tumor tissue, several reports have demonstrated that blood-or urine-based DNA methylation markers could be useful for noninvasive early diagnosis or prognosis of cancers such as prostate, bladder, colorectal, lung, and breast, 21,22 highlighting a logical next step for our studies with PRCC.…”
Section: Discussionmentioning
confidence: 88%
“…Because the sample size of type 2 PRCC from TCGA-KIRP is small, we have not divided samples into training and validation sets, thus the differentially methylated sites we identified require validation as part of future studies. In addition, while the DNA methylation markers in our present study were identified from tumor tissue, several reports have demonstrated that blood-or urine-based DNA methylation markers could be useful for noninvasive early diagnosis or prognosis of cancers such as prostate, bladder, colorectal, lung, and breast, 21,22 highlighting a logical next step for our studies with PRCC.…”
Section: Discussionmentioning
confidence: 88%
“…Few DNA methylation tests investigated for prostate cancer diagnosis. GSTP1 methylation was tested in multiple studies showing sensitivity and specificity as a single gene urine biomarker of 52% and 89%, respectively . With highly sensitive new techniques such as next‐generation sequencing, increasing sensitivity should be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…MGMT in Gliomas (Weller et al, 2010). Some studies have also described value of SFRP1 as prognostic/predictive biomarker in cancer (Leygo et al, 2017;Zheng et al, 2015). The aim of our study was to look for promoter hypermethylation of SFRP1 gene in CRC, and find its prognostic significance.…”
Section: Prognostic Relevance Of Sfrp1 Gene Promoter Methylation In Cmentioning
confidence: 99%